Bones of a feather - Haines, Carolyn (Haines, Carolyn. Sarah Booth Delaney mystery., 2011)
Suspecting that a wealthy new client might be committing fraud through her claim about a stolen necklace worth millions, private investigator Sarah Booth Delaney investigates the sordid past of the woman's family and faces a difficult choice when the woman herself goes missing.